IMPROVING SHORT STORY WRITING SKILLS CLASS VII H STUDENTS IN SEMESTER 1 OF SMP NEGERI 7 KUNINGAN USING THE METHOD CONFERENCE WRITING TAHUN PELAJARAN 2016/2017 - kasih esih (The University of Kuningan, 2022)
In essence, learning a language is learning communication. Therefore, learning Indonesian one of which is directed at improving student's writing skills in communicating with Indonesian both orally and in writing. The conference Writing method is one of the methods or approaches to improve short story writing. The method in this study uses a qualitative approach with a class action research design, which is carried out cyclically—cycle I with planning, action, Observation and reflection. So do subsequent cycles. In PTK as well as teachers can research for themselves their own activities carried out in their own classrooms. By involving its students through actions that are planned, implemented and evaluated. Then the results of the study are as follows 1) The ability of students to write short stories in class VII H of SMP Negeri 7 Kuningan before using the conference writing method (co-writing) is categorized as sufficient with the average score of the class: 65 (not yet completed). 2) There is an increase in the ability to write short stories with the conference writing method (co-writing). Students of class VII H SMP Negeri 7 Kuningan are categorized as good, with an average score of 78 (complete). The ability increases in cycle II and cycle III. In cycle II, the average grade is 72 (not yet completed), and in cycle III, it reaches an average score of 78 (completed), as much as 80% of 41 students. The material was suitable for writing experiential short stories for students of SMP Negeri 7 Kuningan is material that is in accordance with the conditions, desires, experiences, and ability to write short stories.